Avibacterium paragallinarum, the Causative Agent of Infectious Coryza: A Comprehensive Review - El-Gazzar, Mohamed (2025)
Infectious coryza (IC) caused by Avibacterium paragallinarum (AP) has risen in importance as a poultry disease over the past several years because of its increased incidence in commercial poultry in both Europe and the United States. Because of this rise in importance, more attention has been focused on diagnosis, isolation, and surveillance of this bacterial pathogen. As a result, new knowledge has been produced and published. This review was compiled with the main purpose of summarizing and presenting the updated knowledge available about AP. However, the new knowledge can only be understood in the context of previously known facts about the disease. Therefore, this review has been organized in two major parts. The first part is a review of the established knowledge about AP, followed by recent updates. In the first part, we summarize the established well-known as well as some of the less-known facts and literature about AP. The second section focuses on specifics of the latest IC outbreaks in commercial poultry in northern latitudes, particularly in Europe and in North America. Additionally, we reviewed the current geographical distribution of the disease in Asia, South America, and Africa. The crises created by emerging or re-emerging disease outbreaks ignite interest in understanding the disease and pathogen in order to combat it properly. This results in new knowledge that improves the understanding of the disease features, leading to improved disease prevention, control, and eradication. Although knowledge about AP has advanced, knowledge gaps about the disease still persist. Therefore, this review concludes with summarizing the current knowledge gaps as well as potential areas for future research.